Buffering the Impact of Loneliness on Academic Stress: The Moderating Power of Self-Compassion - Devie Yundianto; Zuniyanti Khoiriyah; Rangkuti, Anna Armeini; Khatami, Muhammad; Azam, Uzma (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The COVID-19 pandemic has reshaped students’ academic environments, increasing psychological vulnerability due to prolonged social isolation and rising academic demands. This study explores how loneliness contributes to academic stress and whether self-compassion can buffer this relationship. While previous studies have examined loneliness and self-compassion independently, this study uniquely integrates both constructs into a unified model and tests the moderating role of self-compassion-a relationship that has rarely been empirically explored. Using a quantitative method with convenience sampling, data were collected from 88 university students in Indonesia aged 18-25 years. Participants completed standardized scales measuring loneliness, academic stress, and self-compassion via an online form. Multiple regression and moderation analyses revealed that loneliness positively predicted academic stress, while self-compassion had a negative effect. Importantly, self-compassion significantly moderated the impact of loneliness on academic stress, confirming its buffering role across low, moderate, and high levels. These findings demonstrate that self-compassion functions as an emotional coping resource capable of reducing stress associated with social isolation. This study contributes to the literature by addressing a key gap concerning the interaction between social and intrapersonal factors in predicting academic stress, and it offers practical implications for psychological support strategies in academic settings.